SOCS3 and IL-6 mRNA levels in PBMC enhance the early prediction for patients with acute-on-chronic hepatitis B liver failure receiving glucocorticoid therapy - Li, Ji-Hui; Wang, Jing; Zhu, Han-Xu; Zhang, Feng; Tang, Yu-Na; Wang, Jing-Wei; Fan, Yu-Chen; Liu, Hui-Hui; Wang, Kai (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionEarly prediction is essential in hepatitis B virus-related acute-on-chronic liver failure (ACHBLF) patients receiving glucocorticoid therapy. Interleukin (IL)-6 is the main factor of cytokine storm that occurs in ACHBLF. IL-6 and suppressors of cytokine signaling 3 (SOCS3) may be associated with the prognosis of patients. Peripheral blood mononuclear cells (PBMCs), which are related to the immune response and inflammation of patients, are often used as materials for searching for biomarkers to predict ACHBLF. We aimed to determine serum cytokines levels and to evaluate the prediction value of SOCS3 and IL-6 mRNA levels in PBMC for ACHBLF patients with glucocorticoid therapy.MethodsEighty-five patients with ACHBLF, fifty with pre-ACHBLF, fifty with CHB and thirty healthy controls (HCs) were enrolled. ACHBLF and pre-ACHBLF patients (n=135) received standard medical treatments (SMT) and 93 of them treated with glucocorticoids (SMT+GC). Serum cytokines levels, SOCS3 and IL-6 mRNA levels in peripheral blood mononuclear cells (PBMCs) were quantified.ResultsSerum IL-6, IL-1ß, IL-18 and TNF-α levels of non-survivors with glucocorticoid therapy were significantly higher than that of survivors. Serum IL-10 levels in the survivors with glucocorticoid therapy were significantly increased. The analysis of variable importance shows that IL-6 ranks first. SOCS3 and IL-6 mRNA levels in PBMCs were significantly higher in ACHBLF patients than those in pre-ACHBLF patients (p=0.0158; p=0.0421). Non-survivors showed significantly lower SOCS3 levels (p=0.0084) and higher IL-6 levels (p<0 .0001) than survivors in ACHBLF patients. Non-survivors in patients receiving GC therapy had significantly lower SOCS3 levels (p=0.0002) and higher IL-6 levels (p<0 .0001) than survivors.SOCS3 and IL-6 mRNA levels were predictors for 90-day prognosis of patients receiving GC therapy (p=0.003; p=0.002). AUC of MELD score+SOCS3+IL-6 was 0.887 (95%CI, 0.818-0.955) and the optimal cut-off value was 0.29, with sensitivity of 93.3%, specificity of 74.6%. Patients receiving GC therapy with MELD score+SOCS3+IL-6=0.29 had a higher risk of poor prognosis (p<0 .0001). Survival rate in the SMT+GC group was higher than that in the SMT group (p=0.0350).DiscussionGlucocorticoid treatment could reduce the mortality of ACHBLF. SOCS3 and IL-6 mRNA combined with MELD score could be used to predict for ACHBLF patients receiving glucocorticoid therapy.